Immunomodulatory effect of efferocytosis at the maternal–fetal interface - Hui Tao; Ruilin Ma; Jianjian Cui; Zejun Yang; Wencong He; Yanan Li; Yin Zhao (Cell Communication and Signaling)
Abstract Efferocytosis is a mechanism by which phagocytes efficiently clear apoptotic cells, averting their secondary necrosis and the subsequent release of potentially immunogenic or cytotoxic substances that can trigger strong immune and inflammatory responses. During efferocytosis, the metabolic pathways of phagocytes are transformed, which, along with the catabolism of apoptotic cargo, can affect their function and inflammatory state. Extensive apoptosis occurs during placental development, and some studies reported the immunomodulatory effects of efferocytosis at the maternal–fetal interface. The dysregulation of efferocytosis is strongly linked to pregnancy complications such as preeclampsia and recurrent spontaneous abortion. In this review, we discuss the mechanisms of efferocytosis and its relationships with metabolism and inflammation. We also highlight the roles of professional and non-professional phagocytes in efferocytosis at the maternal–fetal interface and their impact on pregnancy outcomes and explore relevant regulatory factors. These insights are expected to guide future basic research and clinical strategies for identifying efferocytosis-related molecules as potential predictors or therapeutic targets in obstetric diseases.